Knowledge Sharing: Organizational Culture And Transformational Leadership - Mushtaq, Rabia; Bokhari, Rahat Hussain (Journal of Knowledge Management Practice, 2011)
In existing study, relationship among organizational culture, transformational leadership and outcome such as knowledge sharing has been identified. Theoretical framework was proposed to explain the impact of both organizational culture and transformational leadership on knowledge sharing. Data collected from banking sector in Pakistan with a sample size of 116 responses from independent measures. In order to test the theoretical model, multiple linear regression analysis was used leading to hypotheses to be tested. The findings depict that organizational culture and transformational leadership have a positive influence on knowledge sharing in organizations in the banking sector of Pakistan. Organizational culture and leadership style both play a vital role in promoting knowledge sharing activity among the employees.